Pengaruh Kecenderungan Mengambil Resiko terhadap Intensi Berwirausaha dengan Mediasi Efikasi Diri Kewirausahaan - Kurjono, Kurjono; Abdullah, Sulthan Yusuf; Nurlatifah, Nurlatifah (Universitas Galuh, 2025)
This study explicitly aims to analyze the effect of risk-taking propensity on entrepreneurial intention, with self-efficacy as a mediating variable. The research employed a quantitative method using a survey approach and SEM-PLS analysis. Data were collected from 119 randomly selected respondents at the Faculty of Economics and Business Education, Universitas Pendidikan Indonesia (UPI). The results indicate that risk-taking propensity has a positive and significant effect on both self-efficacy and entrepreneurial intention. Self-efficacy also positively influences entrepreneurial intention and partially mediates the relationship between risk-taking propensity and entrepreneurial intention. The implications of these findings highlight the importance of strengthening self-efficacy in entrepreneurship education, for example through field interviews or inviting entrepreneurship practitioners as guest speakers.